1997
DOI: 10.3109/07420529709001417
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four-Hour Rhythms of Serum Acth, Prolactin, Growth Hormone, and Thyroid-Stimulating Hormone, and of Median-Eminence Norepinephrine, Dopamine, and Serotonin, in Rats Injected with Freund's Adjuvant

Abstract: The effect of Freund's adjuvant injection on 24-h variation of circulating ACTH, prolactin, growth hormone (GH), and thyroid-stimulating hormone (TSH) levels, and of norepinephrine (NE) content, and dopamine (DA) and serotonin (5HT) turnover in median eminence, was examined in adult rats kept under light between 0800 and 2000 h daily. Groups of 6-10 animals received Freund's complete adjuvant or its vehicle at 1100 h 3 days before sacrifice and were killed by decapitation at six different time intervals throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
18
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 35 publications
7
18
0
Order By: Relevance
“…We previously reported changes in the 24-hour rhythms of adenohypophysial hormone release and hypothalamic monoamine and neuropeptide content during Freund's adjuvant arthritis in rats. Our results were compatible with significant effects of immunemediated inflammatory response on hormone secretory processes, which were partially sensitive to immunosuppression by cyclosporine [24][25][26]. These as well as other studies indicated that significant changes in 24-hour rhythms did occur during experimental arthritis in rats [27][28][29][30][31][32][33][34][35].…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…We previously reported changes in the 24-hour rhythms of adenohypophysial hormone release and hypothalamic monoamine and neuropeptide content during Freund's adjuvant arthritis in rats. Our results were compatible with significant effects of immunemediated inflammatory response on hormone secretory processes, which were partially sensitive to immunosuppression by cyclosporine [24][25][26]. These as well as other studies indicated that significant changes in 24-hour rhythms did occur during experimental arthritis in rats [27][28][29][30][31][32][33][34][35].…”
Section: Introductionsupporting
confidence: 88%
“…Changes in cir-Esquifino/García Bonacho/Arce/Cutrera/ Cardinali cadian rhythms are apparent at an early phase of experimental arthritis in rats and persist thereafter [29][30][31][32]46]. In previous studies we reported significant effects of immune-mediated inflammation on 24-hour variations of ACTH, GH, LH, testosterone, prolactin and TSH release after Freund's adjuvant injection to young adult [24,25] and old rats [33]. In old rats, 24-hour rhythms of circulating TSH, LH and testosterone became blunted.…”
Section: Discussionmentioning
confidence: 99%
“…In every case, mesor and amplitude of 24-hour rhythm in ornithine decarboxylase activity were lowest in old rats. In a previous study carried out 3 days after Freund’s adjuvant injection in rats, increased levels and a modified 24-hour rhythmicity of circulating ACTH, and abolition of 24-hour rhythmicity of circulating thyroid-stimulating hormone were reported [46]. Presumably, the chronic stress condition given by mycobacterial adjuvant injection is instrumental in inhibiting a number of circadian rhythms at an early, as well as a late, phase of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in serum growth hormone (GH) and pituitary GH mRNA has been described during the early phase before and after the disease develops (Neidhart & Flückiger 1992, Selgas et al 1997. We have recently reported that the decrease in GH mRNA is concomitant with a decrease in serum and hepatic insulinlike growth factor-I (IGF-I) that correlates with the decrease in body weight in arthritic rats (López-Calderón et al 1999).…”
Section: Introductionmentioning
confidence: 99%